Maqasid Syari’ah : Pemenuhan Hak Anak Akibat Orang Tua Berhadapan Dengan Proses Hukum - Hidayat; Dhiauddin Tanjung (Journal Khafi : Journal Of Islamic Studies, 2023)
This research aims to analyze the rights children obtain when their parents are undergoing legal proceedings, especially as perpetrators of crimes. Basically, parents are the main pillars in fulfilling children's rights. However, on the one hand, these rights do not work well because the parents are currently undergoing legal proceedings so that the child's rights are not fully fulfilled. Currently, various parties often ignore the fulfillment of children's rights when parents are undergoing legal proceedings, even law enforcement officials or the government do not pay attention. These rights should be obtained so that children can develop as the nation's next generation. This research uses a type of juridical-empirical research with a legislative and case study approach. This research uses descriptive analysis with a maqasid sharia perspective. As for the results and conclusions of this research, responsibility for fulfilling children's rights does not only lie with the government, but also with other parties so that children's rights when their parents are undergoing legal proceedings can be fulfilled. This is deemed necessary as the aim of maqasid sharia is to protect and preserve the child's mind, religion, soul, property and descendants. Therefore, if a child's parents are facing a legal process, there are children's rights that must be fulfilled based on statutory mandates.